Suplementação alimentar com vitamina C e desempenho zootécnico de girinos de rã-touro (Rana catesbeiana) - Colombano, Neidison Carneiro [UNESP] (2005)
The present study evaluated the effects of vitamin C supplementation about the performance indexes of bull frog tadpoles (Rana catesbeiana) with middleweight of 0,0123g ± 0,002g. Distributed in four groups, allocated in 16 boxes of water proof (40 L), the density was of 1 tadpole L-1, The animals received diet supplemented with zero (control), 1,000, 1,500 e 2,000 mg of vitamin C Kg-1 of food, constituting the groups T1, T2, T3 e T4, for 75 days. They were evaluated in this survival rate, tadpole percentage that were metamorphosed in imago, weight gain, specific growth rate and cells differential counting in the blood. The results showed: the best survival rate (93%), the best tadpoles percentage that were metamorphosed in imago (29%), the biggest weight gain of the tadpoles (4,22g), and the best rate of specific growth (6,03%), was observed in the tadpoles that received a supplementation of 2,000mg vit C kg-1 ration. The worst performance was observed in the tadpoles that did not receive vitamin C. Significant difference in the cells differential counting was not observed (Leukocytes and trombocytes) among different treatments. The results suggest that 2000mg of vitamin C Kg-1 is a good option to improve the weight gain indices, specific growth rate, tadpoles percentage that were metamorphosed in imago and survival rate of the frog-bull tadpoles creation